PLASMA PROCALCITONIN AS A DIAGNOSTIC MARKER FOR ACUTE COMPLICATED APPENDICITIS - A CLINICAL EVALUATION - KUMARESH PANDIAN; MUTHURENGANATHAN PALANIAPPAN; RAJA SENTHIL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Acute appendicitis is a common abdominal emergency requiring timely diagnosis and management. Differentiating between uncomplicated and complicated appendicitis can be challenging using traditional clinical evaluations, imaging, and inflammatory markers. Plasma procalcitonin (PCT), a biomarker associated with bacterial infections, has emerged as a promising tool for identifying complicated appendicitis. This study aims to evaluate the diagnostic efficacy of PCT in distinguishing complicated from uncomplicated acute appendicitis. Methods: This observational study included 120 adult patients diagnosed with acute appendicitis at a tertiary care hospital between March 2022 and December 2022. Plasma PCT levels were measured on admission using Enzyme-linked immunosorbent assay and intraoperative findings and histopathological examinations were used to confirm the severity of appendicitis. PCT levels >0.66 ng/mL were considered indicative of complicated appendicitis. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated to assess the diagnostic performance of PCT. Results: Of the 120 patients, 76 (63.3%) were diagnosed with complicated appendicitis, whereas 44 (36.7%) had uncomplicated appendicitis. Elevated PCT levels (>0.66 ng/mL) were significantly associated with complicated cases, showing a sensitivity of 81.58% and specificity of 77.27%. The PPV was 82.1% while the NPV was 76.6%. The receiver operating characteristic analysis yielded an area under the curve of 0.84, indicating good diagnostic accuracy. Conclusion: Plasma PCT is a valuable diagnostic tool for predicting complicated appendicitis, offering higher sensitivity and specificity compared to traditional markers such as C-reactive protein and white blood cell. Integrating PCT measurements into routine diagnostic protocols can improve clinical decision-making, enabling timely surgical intervention and better resource allocation. Future research should focus on standardizing PCT thresholds and validating its utility across diverse populations.